Ergodicity Breaking Under Confinement in Cold-Atom Quantum Simulators - Jean-Yves Desaules; Guo-Xian Su; Ian P. McCulloch; Bing Yang; Zlatko Papić; Jad C. Halimeh (Quantum, 2024)
The quantum simulation of gauge theories on synthetic quantum matter devices has gained a lot of traction in the last decade, making possible the observation of a range of exotic quantum many-body phenomena. In this work, we consider the spin-$1/2$ quantum link formulation of $1+1$D quantum electrodynamics with a topological $θ$-angle, which can be used to tune a confinement-deconfinement transition. Exactly mapping this system onto a PXP model with mass and staggered magnetization terms, we show an intriguing interplay between confinement and the ergodicity-breaking paradigms of quantum many-body scarring and Hilbert-space fragmentation. We map out the rich dynamical phase diagram of this model, finding an ergodic phase at small values of the mass $μ$ and confining potential $χ$, an emergent integrable phase for large $μ$, and a fragmented phase for large values of both parameters. We also show that the latter hosts resonances that lead to a vast array of effective models. We propose experimental probes of our findings, which can be directly accessed in current cold-atom setups.